Low variation in ribosomal DNA and internal transcribed spacers of the symbiotic fungi of leaf-cutting ants (Attini: Formicidae) - Silva-Pinhati A.C.O.; Bacci Jr. M.; Hinkle G.; Sogin M.L.; Pagnocca F.C.; Martins V.G.; Bueno O.C.; Hebling M.J.A. (Brazilian Journal of Medical and Biological Research, 2004)
Leaf-cutting ants of the genera Atta and Acromyrmex (tribe Attini) are symbiotic with basidiomycete fungi of the genus Leucoagaricus (tribe Leucocoprineae), which they cultivate on vegetable matter inside their nests. We determined the variation of the 28S, 18S, and 5.8S ribosomal DNA (rDNA) gene loci and the rapidly evolving internal transcribed spacers 1 and 2 (ITS1 and ITS2) of 15 sympatric and allopatric fungi associated with colonies of 11 species of leafcutter ants living up to 2,600 km apart in Brazil. We found that the fungal rDNA and ITS sequences from different species of ants were identical (or nearly identical) to each other, whereas 10 GenBank Leucoagaricus species showed higher ITS variation. Our findings suggest that Atta and Acromyrmex leafcutters living in geographic sites that are very distant from each other cultivate a single fungal species made up of closely related lineages of Leucoagaricus gongylophorus. We discuss the strikingly high similarity in the ITS1 and ITS2 regions of the Atta and Acromyrmex symbiotic L. gongylophorus studied by us, in contrast to the lower similarity displayed by their non-symbiotic counterparts. We suggest that the similarity of our L. gongylophorus isolates is an indication of the recent association of the fungus with these ants, and propose that both the intense lateral transmission of fungal material within leafcutter nests and the selection of more adapted fungal strains are involved in the homogenization of the symbiotic fungal stock.